A result on generalized derivations on right ideals of prime rings - Demir, C.; Arga, N. (Український математичний журнал, 2012)
Let R be a prime ring of characteristic other than 2 and let I be a nonzero right ideal of R. Also let U be the right Utumi quotient ring of R and let C be the center of U. If G is a generalized derivation of R such that [[G(x), x], G(x)] = 0 for all x ∈ I, then R is commutative or there exist a, b ∈ U such that G(x) = ax + xb for all x ∈ R and one of the following assertions is true:

(1) (a - λ)I = (0) = (b + λ)I for some λ ∈ C,

(2) (a - λ)I = (0) for some λ ∈ C and b ∈ C. Нехай R — просте кiльце, характеристика якого не дорiвнює 2, а I — ненульовий правий iдеал R. Нехай U — праве фактор-кiльце Утумi кiльця R, а C — центр U. Якщо G є узагальненим диференцiюванням R таким, що [[G(x),x],G(x)]=0 для всiх x∈I, то R є комутативним або iснують a,b∈U такi, що G(x)=ax+xb для всiх x∈R i виконується одне з наступних тверджень:
(1)(a−λ)I=(0)=(b+A)Iдля деякогоλ∈C,
(2)(a−λ)I=(0)для деякогоλ∈Cіb∈C.